Geochemical analyses reveal the importance of environmental history for blue carbon sequestration. Issue 7 (21st July 2017) - Kelleway, J. J.; Saintilan, N.; Macreadie, P. I.; Baldock, J. A.; Heijnis, H.; Zawadzki, A.; Gadd, P.; Jacobsen, G.; Ralph, P. J.
Abstract: Coastal habitats including saltmarshes and mangrove forests can accumulate and store significant blue carbon stocks, which may persist for millennia. Despite this implied stability, the distribution and structure of intertidal‐supratidal wetlands are known to respond to changes imposed by geomorphic evolution, climatic, sea level, and anthropogenic influences. In this study, we reconstruct environmental histories and biogeochemical conditions in four wetlands of similar contemporary vegetation in SE Australia. The objective is to assess the importance of historic factors to contemporary organic carbon (C) stocks and accumulation rates. Results from the four cores—two collected from marine‐influenced saltmarshes (Wapengo marine site (WAP‐M) and Port Stephens marine site (POR‐M)) and two from fluvial influenced saltmarshes (Wapengo fluvial site (WAP‐F) and Port Stephens fluvial site (POR‐F))—highlight different environmental histories and preservation conditions. High C stocks are associated with the presence of a mangrove phase below the contemporary saltmarsh sediments in the POR‐M and POR‐F cores. 13 C nuclear magnetic resonance analyses show this historic mangrove root C to be remarkably stable in its molecular composition despite its age, consistent with its position in deep sediments. WAP‐M and WAP‐F cores did not contain mangrove root C; however, significant preservation of char C (up to 46% of C in some depths) in WAP‐F reveals the importance of historic catchment processes to this site. Together, these results highlight the importance of integrating historic ecosystem and catchment factors into attempts to upscale C accounting to broader spatial scales. Key Points: Multiple ecosystem shifts were observed within the surface 1 m of blue carbon sediments Preservation of inputs from prior ecosystem formation can make large contributions to contemporary carbon stocks Heterogeneity of historical influence needs to be accounted for in regional assessments of carbon storage